Effect of Syzygium cumini leaves on laying hens performance and egg quality - FREITAS,EDNARDO R. (2017)
ABSTRACT The aim of this study was to evaluate the effect of Syzygium cumini leaves (SCL) in laying hens diets on productive performance, egg quality and lipid oxidation of yolk. A total of 108 Hysex White laying hens were distributed in a completely randomized design with three treatments and six replicates of six birds each. The treatments consisted of SCL inclusion at dietary levels of 0, 5 and 10 g/kg. There was no significant effect of SCL inclusion on feed intake, laying percentage, weight and egg mass, feed conversion ratio, Haugh units, specific gravity, percentage of yolk, albumen and egg shells and shell thickness. However, the inclusion of SCL significantly influenced the yolk color and yolk lipid oxidation measured by TBARS values. Yolk color increased and TBARS values ​​decreased with the inclusion of SCL. The inclusion of SCL in laying hens diets improves pigmentation and lipid stability of yolk.